Advanced three-dimensional multiphase flow simulation in porous media reconstructed from X-ray Microtomography using the He–Chen–Zhang Lattice Boltzmann Model - Lin, C.L.; Videla, A.R.; Miller, J.D. (Flow measurement and instrumentation, 2010)
Multiphase flow is a subject of significant interest in the processing of mineral resources and to processing industries in general. Multiphase flow is of significance in the transport of reactants during the percolation of leaching solution in heaps, in the melting of metals, in phase transformation, metal foam processes, underground water transport, in gas and oil recovery and in gas sequestration, just to mention a few examples. The lattice Boltzmann model (LBM) of multiphase fluid flow has now become a collection of models with varying degrees of faithfulness to the properties of real fluids. These models are in a state of evolution as they are becoming better understood and are extended to new applications. In this paper we address the application of a single-component multiphase flow LBM known as the He–Chen–Zhang model coupled with X-ray microtomography (XMT) for the digitalization and simulation of flow in porous media. The model is used for the simulation of fluid penetration into porous samples and the analysis of capillary phenomena. Specifically, this model has been applied for the simulation of percolation in a packed bed of sand particles which is digitalized by XMT.